Dominant species play a leading role in shaping community stability in the northern Tibetan grasslands. (2nd January 2023) - Hou, Ge; Shi, Peili; Zhou, Tiancai; Sun, Jian; Zong, Ning; Song, Minghua; Zhang, Xianzhou
Abstract: Dominant species may strongly influence biotic conditions and interact with other species, and thus are important drivers of community dynamics and ecosystem functioning, particularly in the stressed environment of alpine grasslands. However, the effects of dominant species on the community stability of different ecosystems remain poorly understood. We examined the mechanisms underlying temporal stability (2014–2020 year) of aboveground productivity and community stability in four alpine grasslands (alpine meadow, alpine meadow steppe, alpine steppe and alpine desert steppe) of the northern Tibetan with different species composition and dominance. Our results showed that community stability was significantly higher in the alpine meadow than in the other three types of grasslands. This difference was mainly attributed to the higher compensatory effect and selection effect in the alpine meadows. Furthermore, dominant species strongly affected community stability by increasing dominant species stability and species asynchrony. However, species richness had little effect on community stability. Our findings demonstrate that dominant species, as foundation species, may play leading roles in shaping community stability in the alpine grasslands, highlighting the importance of conserving dominant species for stable ecosystem functioning in these fragile ecosystems under increasing environmental fluctuations.